Product review on MAbs (alemtuzumab and ocrelizumab) for the treatment of multiple sclerosis - Tereza Gabelić; Barbara Barun; Ivan Adamec; Magdalena Krbot Skorić; Mario Habek (Taylor & Francis Group, 2021)
Traditionally, the management of active relapsing remitting MS was based on the, so-called, maintenance therapy, which is characterized by continuous treatment with particular disease modifying therapy (DMT), and a return of disease activity when the drug is discontinued. Another approach is characterized by a short treatment course of a DMT, which is hypothesized to act as an immune reconstitution therapy (IRT), with the potential to protect against relapses for years after a short course of treatment. Introduction of monoclonal antibodies in the treatment of MS has revolutionized MS treatment in the last decade. However, given the increasingly complex landscape of DMTs approved for MS, people with MS and neurologists are constantly faced with the question which DMT is the most appropriate for the given patient, a question we still do not have an answer to. In this product review, we will discuss the first DMT that acts as IRT, an anti-CD52 monoclonal antibody alemtuzumab and an anti CD20 monoclonal antibody, ocrelizumab that has the potential to act as an IRT, but is administered continuously. Special emphasis will be given on safety in the context of COVID-19 pandemics and vaccination strategies.